2020
DOI: 10.1007/s00340-020-07519-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the adiabatic and isothermal pressure dependence of the index of refraction in a drop-weight apparatus

Abstract: We have investigated the difference between adiabatic and isothermal compression of liquids by an impacting weight, as observed in the resulting change to the index of refraction. The liquids examined were sebacate, glycerol, and water. For practical reasons, sebacate is best suited for the use of a drop-weight apparatus as a metrologically traceable calibration facility for dynamic pressure. We find that its optical properties under adiabatic and isothermal compression can be converted into each other using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The applicable pressure range of the measurement standard is 60 MPa up to (at least) 400 MPa. An important thing was to investigate the difference between adiabatic and isothermal compression of liquids by an impacting weight, as observed in the resulting change to the index of refraction [9]. It was found that the optical properties under adiabatic and isothermal compression can be converted into each other using literature values of thermodynamic properties.…”
Section: Drop-weight Devices Based On Refractive Index Methodsmentioning
confidence: 99%
“…The applicable pressure range of the measurement standard is 60 MPa up to (at least) 400 MPa. An important thing was to investigate the difference between adiabatic and isothermal compression of liquids by an impacting weight, as observed in the resulting change to the index of refraction [9]. It was found that the optical properties under adiabatic and isothermal compression can be converted into each other using literature values of thermodynamic properties.…”
Section: Drop-weight Devices Based On Refractive Index Methodsmentioning
confidence: 99%
“…The liquids studied were sebacate, glycerol and water. In the study, sebacate was evaluated as the most suitable measuring fluid for dynamic pressure measurements using low weight masses [9]. However, in different studies, glycerol was preferred as the liquid used in the measuring head [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Metrological traceability to the International System of Units (SI) requires the development of appropriate primary standards for dynamic measurements of pressure [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The aperiodic shock tube pressure generators show a potential to provide SI-traceable dynamic calibrations for pressure sensors [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%